Leadership in Early Education in Times of Change Research from five Continents - Heikka, Johanna; Hujala, Eeva; Rodd, Jillian; Strehmel, Petra; Waniganayake, Manjula (International Leadership Research Forum Early Education (ILRFEC) Research monograph, 2019)
The collection brings together the latest work of researchers from Australia, Africa, Asia, and Europe focusing on early childhood leadership matters. It covers different aspects of leadership in early education: professional education and development, identity and leadership strategies as well as governance and leadership under different frame conditions.